Studying the role of spatial cell distribution and substrate stiffness in inflammatory and fibrotic responses in human lung using bioengineered platforms - Htwe, Su Su (2017)
The extracellular matrix (ECM) has emerged as a major regulator of cell behaviours. Changes in extracellular matrix, especially its composition, organization/ dimensionality, and rigidity have been implicated in various aspects of cellular functions including cell growth, migration, and differentiation. In my thesis, I have focused on the effect of two biophysical properties of the extracellular matrix namely dimensionality and rigidity in the inflammatory and fibrotic pathologies of human lung. To study the role of matrix dimensionality, firstly electrospun scaffold based three-dimensional (3D) culture with similar architecture of human lung was developed. By applying this 3D model, inflammatory response was studied in an in vivo like environment by using NF-κB transcription factor activation as a tool for probing inflammatory response in human lung fibroblasts. According to my observations, it was confirmed that the matrix dimensionality together with spatial organisation of cells is crucial in lung inflammatory response, evidenced by the observation of the differences in the level and pattern of inflammatory response between 2D and 3D culture systems. To study the role of matrix rigidity in progression of lung fibrosis, we developed the ECM-based hydrogel platform with tuneable stiffness level relevant to normal and fibrotic lung. By using this disease relevant platform, I have shown that stiff matrix but not soft matrix can induce the myofibroblast differentiation and fibroblast proliferation, the two major features of lung fibrosis. To date, the molecular mechanisms underpinning this cellular mechanosensing process in response to matrix stiffening remains unknown. To achieve this, I further investigated the involvement of two potential mechanosensitive signalling pathways namely, Rho associated coiled coil forming kinase (ROCK) signalling and talin- (focal adhesion adaptor) signalling in this process. Interestingly, my data show that ROCK signalling differentially regulated stiffness induced myofibroblast differentiation between soft normal and stiff fibrotic matrix. Moreover, both ROCK isoforms 1 and 2 are synergistically important in myofibroblast differentiation driven by rigid matrix and the absence of one ROCK isoform can exaggerate myofibroblast differentiation on stiff fibrotic matrix. Regarding talin signalling, my preliminary data confirms that talin1 can control both stiffness induced fibroblast proliferation and myofibroblasts differentiation on stiff matrix. In contrast to talin1, talin2 showed a protective role in controlling myofibroblast differentiation. In conclusion, we have successfully developed two in vitro lung models for studying the effect of matrix dimensionality and rigidity in lung inflammation and fibrosis. Overall my PhD work has elucidated the significant contribution of biophysical cues of external cellular environment in lung inflammation and fibrosis.